Factors Affecting the Financial Performance of Property Andreal Estate Companies Listed at Indonesia Stock Exchange - Deitiana, Tita; Habibuw, Lionel Greg (Asian Business Review, 2015)
Financial performance is one of the factors used by investors in buying shares. For companies, improving financial performance is a must in order to keep the company's stock attractive to investors. Financial statements published by the company are a reflection of the company's financial performance. These financial statements are the result of the accounting process that is intended to provide the financial information of a company. The financial information can be used by users for making investment decisions.Performance is the result of the fulfillment of the tasks assigned. Company performance describes how individualsin the company tries to achieve a goal. Company performance illustrates the magnitude of the results in a process that has been achieved compared with the company’s goal. The purpose of this study is to find out factors determining financial performance.The objects of this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period of 2007 – 2012. Data for this study stems from secondary data gathered by analyzing financial statement of the sample companies. The data is then analyzed with Eviews 7.2 Panel Data Regression Analysis.The research findings can be summarized as follows. Variable leverage and Firm Age has an effect on financial performance. Other variables like liquidity, Firm Size, Managerial Ownership and Block holder Ownership have no effect on financial performance. JEL Classification code: G31
Keywords: Financial Performance; Leverage; Liquidity; Firm Size; Firm Age; Ownership